Fundamentals of Management, Global Edition - Stephen P. Robbins; Mary A. Coulter; David A. DeCenzo (United Kingdom Pearson, 2020)
For undergraduate principles of marketing courses. Everything students need to know to develop their 'management sense' and be successful Fundamentals of Management covers the essential concepts of management by providing a solid foundation for understanding the key issues facing managers and organizations. The 11th Edition maintains a focus on learning and applying management theories, while now also highlighting opportunities to develop the skills in high demand by today's employers. Fundamentals of Management offers an easy-to-understand, straightforward, and realistic approach to what works for managers and what doesn't -- with the ultimate goal to help students be successful in their careers.
Keywords: (UGB-261) Management thought